Microstructural evolution and phase transformation in the liquid-solid Al/Ni diffusion couple. Issue 9 (3rd May 2019) - Zhang, Z.X.; Jiang, H.; Russell, A.M.; Skrotzki, W.; Müller, E.; Schneider, R.; Gerthsen, D.; Cao, G.H.
ABSTRACT: The liquid-solid Al/Ni diffusion couple was successfully fabricated by annealing at 1373 K for 48 h followed by water-quenching. Cross-sectional scanning and transmission electron microscopic analyses show that the multilayered diffusion zones comprise the following sequence of layers: γ-Ni(Al) | γ′-Ni3 Al | β′-NiAl | Ni-rich β-NiAl | β-NiAl. The Ni-rich β-NiAl upon quenching undergoes a martensitic transformation from β (B2) to β′ (L10 ). The β′ martensite is found to be internally twinned on the {111}<112>system. The volume changes and strains due to martensitic phase transformation, the precipitation of γ′-Ni3 Al from γ-Ni(Al) and lattice mismatch between Ni-rich β-NiAl and β-NiAl in the Al/Ni diffusion couple are quantitatively determined. The cuboidal γ′ phase coherently precipitates cube-on-cube in γ-Ni(Al). Composition fluctuations existing in the supersaturated solid solution γ-Ni(Al), provide sufficient driving force for the precipitation and facilitate nucleation and growth of the γ′ phase under isothermal annealing.